ANALYSIS OF CAPACITY BUILDING AND HEADLOSS ON RAW WATER PIPELINENS FOR WATER TREATMENT PLANTS WTP OF GUNUNG LIPAN AT PDAM KOTA SAMARINDA - UDDIN, KAHAR (KURVA S JURNAL MAHASISWA, 2018)
Incrased development along with increasing population growth has led to increased demand for clean water in the Regional Service Zone IV at PDAM Kota Samarinda, so it demands an increase in performance from all aspects, both operational, administrative, and financial aspects. For operational aspects, one of them increasing the production capacity of Water Treatment Plants (WTP). In the IV Area Service Zone there are three WTP which the distribution pipeline network is interconnected. That is WTP Gunung Lipan, WTP Unit 3 Samarinda Seberang dan WTP Palaran with total production capacity of 456,24 L/s. Based an a number reasons WTP Gunung Lipan the most potential to increase production capacity. And the question is what is the production capacity of WTP Gunung Lipan in the next ten years and how much headloss on the raw water pipeline from the intake to WTP right now and the next ten years. Population growth is the basic for planning in determining the amount of clean water needs for the next years. By using arithmetic and geometry methods the population in the year of the plan can be estimated or projected. The calculation of planning for clean water needs is based on the criteria set by Ministry of Public Works Regulation in 1998 which consist of domestic and nondomestic needs. By knowing the amount of need for clean water in the Area IV Service Zone and production capacity of the WTP Gunung Lipan, than the raw water debit (Q) can be obtained. Calculation headloss on the raw water pipe from Intake to WTP based on raw water discharge and pipeline network conditions. The steps taken are calculation of flow velocity (v), minor headloss and major headloss(HL) calculation. Based on the resuts of the analysis and calculation, the production capacity of the WTP Gunung Lipan was obtained from 307,17 L/s in 2018 to 547,006 L/s in 2028. Headloss on the raw water pipe network from the Intake to WTP in 2018 for pumps with a capacity of 110 L/s are 0,878 m, for pumps with a capacity of 220 L/s of 1,597 L/s and the operation of two or three pumps with capacity of 312 L/s headloss of 1,886 m. Lead headloss on the raw water network in 2028 for pumps with capacity of 300 L/s of 2,338 m and the operation of two pumps units with a capacity of 554,7 L/s headloss of 3,299 m